Speech Perception in Children Under Noisy Situations - Jacob, Regina Tangerino de Souza; Monteiro, Natália Fernanda Garro; Molina, Samira Vilela; Bevilacqua, Maria Cecília; Lauris, José Roberto Pereira; Moret, Adriane Lima Mortari (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: The ability to understand speech is impaired by many factors during evaluations, especially under noise, and it is still more complex for children under these conditions.Objective: To analyze the speech perception in children with a normal hearing in different noise situations.Method: Way of study transverse section. The Brazilian Hearing in Noise Test (HINT) was performed in 21 children aged between 7 and 14 with a standard hearing and no cognitive alterations. The sentence lists were randomly used in these situations: silence (S), frontal noise (FN); right-side noise (RN); left-side noise (LN); noise at 180°. (RT) and a comparison between the result of the compound noise (CN) and the diffuse noise in four sound areas at 45°; 135°; 225° e 315° (4 BXS).Results: The statistical analysis showed a significant difference among the following situations: RN with FN; BN with FN; and it was worse with 4 BXS, where a difference for RN, BN, CN, LN and FN was found. To analyze a correlation with age, it was significant regarding the age, as a result of HINT values only for the frontal noise.Conclusion: The significant differences in the results of speech perception among the different hearing conditions in the evaluated individuals suggest carefulness when choosing the stimulus in evaluations of speech perception in the noise in hearing-impaired children. Accordingly, researches in this field are necessary to determine the standards and variations related to its application and result interpretation.
Keywords: audiology; noise; speech perception; speech discrimination test